Optimalisasi Diksi Dan Mengaplikasikan Gambar Sebagai Media Pembelajaran Puisi - Zebua, Kesadaran; Zebua, Aldin (CV. SINAR HOWUHOWU, 2025)
This research describes what are the factors that influence the creation of a poem. Based on the results of the research, one of the problems or challenges that can cause an individual’s inability to write poetry is the low quality of learning. Inappropriate and ineffective learning will make it difficult for a person to create good and correct poetry, as well as difficult to develop creative ideas. Poetry is one of the written literary works of a person that contains certain meanings. As one of the written literary works, poetry can convey the emotions of the author or poet through a series of enchanting words from the imagination of a poet. In addition, writing poetry means creating beautiful sentences, accompanied by semantic meanings that express the feelings, thoughts, and experiences of the author. To be able to create an interesting poem, and rich in semantic meanings (messages), it requires the right choice of words (diction), and the use of image media to help stimulate the imagination. The findings show that diction and image media can influence the creation of a poem, for examples to get ideas and words that are suitable and beautiful for a poem. This article presents the use of diction and applying pictures as learning media to support the creation of a poem. In this study, the researcher used the literature research method. The literature research method is used to analyze academic materials with an emphasis on identifying problems in writing poetry, as well as the role of diction and image media as a solution. The results showed that the mastery of diction and the creative and efficient use of image media can improve poetry writing skills so as to produce meaningful and aesthetic poems.